The efficacy of an online anger management program for justice-involved youth - Braeuer, Katie (Journal of addictions & offender counseling, 2022)
The authors examined the efficacy of online anger management psychoeducation for justice-involved youth. Results indicated a statistically significant decrease in the adolescent anger rating scale for juveniles who completed the mandated program, prompting consideration of online modalities in postpandemic services.